356 DAPAGLIFLOZIN USE IN HEART FAILURE WITH REDUCED EJECTION FRACTION PATIENTS: A SINGLE CENTRE COMPARISON BETWEEN REAL-LIFE AND DAPA-HF DATA. (15th December 2022) - Capovilla, Teresa Maria; Mapelli, Massimo; Mattavelli, Irene; Salvioni, Elisabetta; Marongiu, Alessandro; Maranzano, Gaspare; Vignati, Carlo; Palermo, Pietro; Sinagra, Gianfranco; Agostoni, Piergiuseppe
Abstract: Background: Practice guidelines recommend Sodium-glucose co-transporter-2 inhibitors (SGLT2-i) for patients with heart failure with reduced ejection fraction (HFrEF). This study aimed to describe our population of patients with indications for Dapagliflozin, to compare it with the DAPA-HF trial population and assess the possible prognostic evolution. Methods: We retrospectively analysed clinical data of the first 100 HFrEF patients treated with Dapagliflozin at our heart failure clinic (Centro Cardiologico Monzino) from September 2021. Results: Table 1 shows patient characteristics in our study (n = 100) and in the DAPA-HF trial (n = 2373). Our patients had a mean age of 69±11 years, mean left ventricular ejection fraction of 31, 1±8, 0%, New York Heart Association class II (78%), class III (21%) and class IV (1%). 64% of our patients performed cardiopulmonary exercise test (CPET), with mean peak VO2/kg of 14, 3±4, 5 ml/min/kg and mean VE/VCO2 slope of 39, 1±10, 5. In our study, compared to the DAPA-HF trial population, there were fewer diabetic patients (14, 1% vs 41, 8%, p < 0, 001), a larger number of patients with implanted cardioverter defibrillator (ICD) (59, 6% vs 26, 2%, p < 0, 001) and cardiac resynchronization therapy (CRT) (22, 2% vs 8, 0%, p < 0, 001). Furthermore, our population had a higher percentage of patients already on optimised therapy with Sacubitril/Valsartan (86, 9% vs 10, 5%, p < 0, 001) and mineralocorticoid receptor antagonists (82, 8% vs 71, 5%, p < 0, 001), along with beta-blockers (97, 9% vs 96%, p = 0, 434). Conclusions: Our patients were slightly older and frailer than those in the pivotal DAPA-HF trial and probably at a more advanced stage of the disease as suggested by the higher prevalence of ICD/CRT and Sacubitril/Valsartan. Based on these results, it may be that the expected prognostic benefit of adding Dapagliflozin to their therapy, in terms of absolute risk, will be lower than in the DAPA-HF trial. Future studies and a longer follow-up are needed to compare death and hospitalisation rates.